Strategic Management of Madrasah Principals in Strengthening Human Resources to Improve Educational Quality in Private Madrasahs in Mamuju Tengah Regency - Rosita; Siti Rahmawati (Edumaspul: Jurnal Pendidikan, 2026)
Strategic management by madrasah principals is a critical factor in strengthening human resources and improving educational quality in private madrasahs. This study aims to analyze the strategies used by madrasah principals in planning, organizing, implementing, and evaluating human resource strengthening in private madrasahs in Mamuju Tengah Regency. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving madrasah principals, teachers, educational staff, madrasah committee members, and foundation representatives selected purposively. Data were analyzed through data condensation, data display, conclusion drawing, and verification. The findings show that madrasah principals implemented strategic management through human resource needs analysis, quality-based work program formulation, teacher competency development, optimization of educational staff, academic supervision, work culture development, and collaboration with foundations and the community. Human resource strengthening contributed to improved teacher discipline, learning services, administrative order, work motivation, and public trust. The study concludes that directed, participatory, and sustainable strategic management by madrasah principals can strengthen human resource capacity and support educational quality improvement in private madrasahs.